Improving the awareness of healthy dietary practices and non-communicable diseases among adults in Mbingo community. - Nsang, D'vumbighe Brenda; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student's Journal of Health Research Africa, 2025)
Background Non-communicable diseases have posed a serious health problem both in developed and LMICs. The main NCDs that are diet-related include DM, HTN, CA, CVDs hence NR-NCDs. The dietary factor has been noted with evidence to be the highest contribution to these diseases as a lot of people are relegated to consuming unhealthy diets with many dietary practices that pose health risks. This project aimed at improving the awareness of healthy nutritional practices and non-communicable diseases among adults in Mbingo Community. Results Conducted massive sensitization and education to all adults 18 to 65 years in the MBH community. Provided monthly education in churches, schools, social gatherings, and clinics by trained health and community workers. Training of health professionals and CHWs in behavior and attitude change towards unhealthy dietary practices among adults, Community utilization of NCD services, and Resource mobilization with leadership was done. Conducted massive screening among adults 18 to 65 years in the MBH community and referred diagnosed cases with complications to health facilities for better management and NCD clinics for better networking. Conclusion The NCD problem globally, in Cameroon and MBH community is a crucial issue due to increased morbidity and mortality. Several risk factors have been known to contribute to the incidence and prevalence, with unhealthy dietary risk factors being the most prominent among others. Recommendation The Ministry of Health should set out funds right down to regional levels for Nutrition awareness and campaign programs, and monitor its implementation to ensure that the budgeted funds are used as planned.